The waitress [videorecording (DVD)] - Shelly, Adrienne, 1966-2006; Russell, Keri, 1976-; Fillion, Nathan, 1971-; Hines, Cheryl (20th Century Fox Home Entertainment, 2007)
Jenna is unhappily married. She squirrels away money and is hoping to win a pie-baking contest so, with the prize money, she'll have enough cash to leave her husband Earl. She finds herself pregnant and her plans are thrown awry. She bakes phenomenal pies at Joe's diner, listens to old Joe's wisdom, tolerates her sour boss Cal, is friends with her fellow waitresses, Dawn and Becky. She, also, finds a mutual attraction with the new doctor in town. Life with Earl becomes less tolerable as her pregnancy advances. Her way out of the marriage is less clear and her affair with the doctor is complicated by his marriage.